Rays of Change: Commentary on Potential Interventions for Skin Cancer Prevention in Ontario Medical Education - Aliyah King; Reetesh Bose (University of Ottawa Journal of Medicine)
This commentary addresses the rising incidence of skin cancer in Ontario and the exclusion of Skin of Colour (SOC) populations from sun-protection advocacy. It proposes the installation of sunscreen dispensers in medical schools to promote sun safety habits and awareness among future healthcare providers. The initiative aims to reduce skin cancer rates by normalizing sunscreen use across all skin types, with educational infographics emphasizing SOC needs. Despite potential barriers such as cost and community resistance, the involvement of healthcare professionals and students could drive long-term change in sun-protective behaviors and improve population health outcomes.